Study on histogenesis of enterochromaffin-like carcinoid in autoimmune atrophic gastritis associated with pernicious anemia - Mačukanović-Golubović Lana; Katić Vuka; Rančić Gorana; Milenović Mladen; Marjanović Goran; Golubović Zoran (Vojnosanitetski Pregled)
Background/Aim. Autoimmune atrophic fundic gastritis induces the pernicious anemia (PA), as well as the changes in both epithelium and endocrine cells of gastric mucosa. The most important complications are: achlorhydria, hypergastrinemia, gastric cancer and enterochromaffin-like ( ECL) carcinoid. The aim of this study was to examine ECL carcinoid histogenesis in A-gastritis associated with PA. Methods. During the period from 2000−2006, 65 patients with PA and 30 patients of the control group were examined. Histopathological examination was done in endoscopical biopsies of gastric mucosa fixed in 10% formaldehyde. Paraffin sections were stained with classic hematoxylin-eosin (HE); histochemical AB-PAS (pH 2.5), cytochemical argyrophilic Servier-Munger′s and immunocytochemical PAP methods for G cell identification and chromogranin A antibodies - specific marker for neuroendocrine ECL cells. Both G and ECL cells were counted per 20 fields, of surface 0.0245312 mm2 by a field. Basal gastrin serum levels were also examined by using radioimmunoassay (RIA) method. The obtained results were statisticaly calculated by using Student΄s t test. Results. Marked antral G cell hyperplasia associated with corporal ECL hyperplasia was found. ECL cell hyperplasia was of simplex, linear, adenomatoid type to the pattern of intramucous ECL cell carcinoid. An average number of G cells was statistically significant in the patients with PA as compared to the control group (p < 0.05) as well as an average number of ECL cells. Conclusion. We concluded that antral G cell hyperplasia accompanied by gastrinemia induces ECL hyperplasia and ECL corporal carcinoid in A-gastritis and that their histogenesis develops trough simple, linear and adenomatoide hyperplasia. .